Dr. Oszkár Tóth awarded by „Antal Gulyás medallion for crop protection“ in 2011 (laudation) - Kövics, György (Acta Agraria Debreceniensis, 2011)
The Public Utility for Development of Crop Protection Teaching (NOFKA) and The Hajdú-Bihar County Regional Association of Hungarian Chamber of Crop Protection Specialists and Plant Doctors (Chamber) established a joined Award Committee in September of 2011, which intend to serve as moral appreciation to prominent persons with excellent achievements by awarding the „Antal Gulyás medallion for crop protection” which are available for outstanding teachers, researchers, and practical crop protection specialists. The biography of late Antal Gulyás distinguished professor of plant pathology is available in a separate article of this issue. The first person to be decorated with the „Antal Gulyás medallion for crop protection” is Dr Oszkár Tóth retired reader of plant pathology for his excellence in teaching crop protection. Dr Oszkár Tóth had been involved in teaching - by delivering both lectures and practical lessons - crop protection, namely plant pathology in the legal predecessor institute of Debrecen University for more than 30 years where generations of crop protection specialists were encouraged to get a thorough knowledge in plant pathology. The one-time students of the splendid teacher welcome and congratulate to the award, moreover wish him peaceful and happy years.